China-Russia cooperation determining factors, future trajectories, implications for the United States - Radin, Andrew; Scobell, Andrew; Treyger, Elina; Williams, J. D.; Ma, Logan; Shatz, Howard J.; Zeigler, Sean M.; Han, Eugeniu; Reach, Clinton Bruce (Rand Corporation, 2021)
China and Russia are perceived as major, long-term competitors with the United States. Since 2014, China and Russia have strengthened their relationship, increasing political, military, and economic cooperation. In this report, the authors seek to understand the history of cooperation between Beijing and Moscow, the drivers of and constraints on the relationship, the potential future of cooperation between China and Russia, the impact of the Chinese-Russian relationship on the United States, and implications for future U.S. policy. The authors find that the main motivations for closer 21st century cooperation between China and Russia are the declining relative power of the United States and the persistent perceived threat from the United States to both China and Russia. If current trends continue, the authors expect the collaborative relationship between China and Russia to be sustained. Absent major (and likely undesirable) changes in U.S. policy, there is little the U.S. government or Army can do to influence the trajectory of the China-Russia relationship. The U.S. military can prepare for the results of greater Sino-Russian cooperation, including by expecting further diffusion of Chinese and Russian military equipment, additional joint planning and exercises, potential joint basing, and eventually the possibility of joint military operations.--page 4 of cover
"RR-3067-A" -- Page 4 of cover
Prepared for the United States Army
Keywords: Geschichte 1997-2017; Internationale Politik; Kooperation; China; Russland; Russia / Foreign relations / China; China / Foreign relations / Russia; China / Foreign relations / United States; Russia / Foreign relations / United States; United States / Foreign relations / China; United States / Foreign relations / Russia; International economic relations; Russia; Diplomatic relations; United States